Istikhdam Flashcards li Isti‘abi ‘ala al-Mufradat fi Madrasati Tri Bhakti at-Takwa ats-Tsanawiyyah Raman Utara Lampung - Dian Risky Amalia; Indra Pranata; Rizky Hidayatullah (Postgraduate of IAIN Metro Lampung Indonesia, 2019)
In teaching Arabic language it is necessary to use teaching aids, because it is a foreign language. Therefore, the teacher must use it in learning. The purpose of this study was to determine the effect of the use of flashcards for seventh grade students in the Junior High School Tri Bhakti at-Taqwa Rama Puja Dance for the 2018/2019 academic year. The kind of research is experiment. This research choose pseudo experiment methods in the form of experiment control and non-control, and to overcome the researchers’ data using tests, documents and observations. The data analysis methode is the Lilliefors method based on calculations and based on calculations before the normal life test of experimental separation is 0.152 and the adjuster is 0.149. A significant level of 0.05% indicates that the two study samples were normally distributed, and then the calculation testing the normal life of the experiment separation was 0.286. And the non-control class was 0.192, and a significance level of 0.05% showed that the two study samples were normally distributed. This 2,065 <1,771. So the data can be concluded that we tested the normal distribution. An alternative hypothesis is the influence of the use of flashcards to master the vocabulary of seventh semester students in the Tri Bhakti Junior High School Rama Puja for the academic year 2018/2019 is a profoundly acceptable effect.